ТЕРМООБРАБОТАННЫЙ ТУФФИТ – В КАЧЕСТВЕ ГИДРАВЛИЧЕСКОЙ ДОБАВКИ ДЛЯ ПОРТЛАНДЦЕМЕНТА - Кабулова, Л.К.; Атакузиев, Т.А.; Оразимбетова, Г.Ж.; Избасарова, Г.Б. (SCIENCE and SOCIETY, 2022)
The article examines the suitability of tuffite mineral in Portland cement for use as a hydraulic additive and, as a result, the durability of Portland cement under sulfate and sulfate-magnesium corrosion resistance